Entropy of fermionic models on highly frustrated lattices - Honecker, A.; Richter, J. (Condensed Matter Physics, 2005)
Spinless fermions on highly frustrated lattices are characterized by the lowest
single-particle band which is completely flat. Concrete realizations are
provided by the sawtooth chain and the kagome lattice. For these models ´
a real-space picture is given in terms of localized states. Furthermore, we
find a finite zero-temperature entropy for a suitable choice of the chemical
potential. The entropy is computed numerically at finite temperature
and one observes a strong cooling effect during adiabatic changes of the
chemical potential. We argue that the localized states, the associated zerotemperature
entropy as well as the large temperature variations carry over
to the repulsive Hubbard model. The relation to flat-band ferromagnetism
is also discussed briefly. Безспінові ферміони на сильно розвпорядкованих гратках характеризуються найнижчою одночастинковою зоною, яка є повністю
плоскою. Конкретні реалізації зроблені за допомогою пилкоподібного ланцюжка та гратки Кагоме. Для цих моделей приведено
картину в дійсному просторі в представленні локалізованих станів.
Далі ми знаходимо скінчену ентропію при нульовій температурі
для певного вибору хімічного потенціалу. Ентропія розраховується чисельно при скінченій температурі і спостерігається сильний
ефект охолодження під час адіабатичних змін хімічного потенціалу.
Ми аргументуємо, що локалізовані стани, відповідна ентропія при
нульовій температурі як і сильні варіації температури переносяться на модель Габбарда з відштовхуванням. Коротко обговорюється
також зв’язок із феромагнетизмом плоских зон.